Sejarah dan Perbandingan Pendidikan Negara Brazil dan Saudi Arabia - Bujang Ruslan; Fadli Afriansyah; Hery Noer Aly; Zulkarnain Zulkarnain; Ismail Ismail (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is to compare the education sistem in Brazil with a communist figure named Paulo Freire with the Government Sistem of the State of Saudi Arabia (Islam), the Holy Qur'an and the Sunnah of the Prophet Muhammad SAW. The research method and the type of data collection in this research is library research. The analysis technique uses a descriptive analysis approach by reducing data from library sources. The results of the study in Brazil have a federal government sistem, a republican government sistem , unions, federal districts and cities in managing and regulating the education sistem . Saudi Arabia is a royal state. The education sistem is more about the Islamic religion and is regulated by the organization The General Presidency of Girls' Education (GPGE). The conclusion is that Brazil applies the education sistem . Freire's concept of critical literacy education aims to raise critical awareness of the oppressed to the reality of oppression that has shackled them as human beings. Meanwhile, Saudi Arabia has an education sistem known as “The General Presidency of Girls' Education” (GPGE). Keywords: Brazil and Saudi Arabia, Multicultural Education.